Learning from Imbalanced Data in Presence of Noisy and Borderline Examples - Napierała, Krystyna; Stefanowski, Jerzy; Wilk, Szymon (Rough Sets and Current Trends in Computing, 2010)
In this paper we studied re-sampling methods for learning classifiers from imbalanced data. We carried out a series of experiments on artificial data sets to explore the impact of noisy and borderline examples from the minority class on the classifier performance. Results showed that if data was sufficiently disturbed by these factors, then the focused re-sampling methods – NCR and our SPIDER2 – strongly outperformed the oversampling methods. They were also better for real-life data, where PCA visualizations suggested possible existence of noisy examples and large overlapping ares between classes.